2021
DOI: 10.3389/fenrg.2021.649163
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Energy in Export Flows Along Global Value Chain: A Case Study of China’s Export Trade

Abstract: Energy issues are closely related to the development of human society and economy. Embodied energy is the total direct and indirect energy consumption required for the production of goods and services. In the context of the intensifying development of economic globalization and prosperity of international trade, embodied energy is considered as a better indicator to comprehensively reflect the nature of a country’s energy use than the direct energy use. The development of trade in value added (TiVA) accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This implies that relying on cost advantages from labor market distortion would enable these markets to participate in global value chains and reap profits rather than depending on productivity and innovating organizational management to gain international competitiveness (Gao & Yuan, 2022). This incentive may impede the shift to higher value‐added segments, thus discouraging export trade upgrading (Zhang et al, 2021; Zheng et al, 2022). The above analysis leads to Hypothesis 4.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…This implies that relying on cost advantages from labor market distortion would enable these markets to participate in global value chains and reap profits rather than depending on productivity and innovating organizational management to gain international competitiveness (Gao & Yuan, 2022). This incentive may impede the shift to higher value‐added segments, thus discouraging export trade upgrading (Zhang et al, 2021; Zheng et al, 2022). The above analysis leads to Hypothesis 4.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…By identifying the resource, energy consumption, and pollution emissions of each link, we can target high-energy consumption and high-pollution processes, increase green R&D investment, and introduce high-end cleaner production technology to achieve energy conservation and emission reduction (Cui, 2020). The optimizing of China's export embodied energy structure is conducive to global energy conservation and emission reduction (Zhang et al, 2021). Generally, multinational corporations in developed countries implement global unified environmental standards, which naturally have a joint impact on the transformation of green achievements of upstream and downstream enterprises.…”
Section: Green Achievement Transformation Stagementioning
confidence: 99%
“…By using trade between China and the USA as an example, Xu et al ( 2009 ) demonstrated that carbon dioxide emissions embodied in the exports from China to the USA represented approximately 8–12% of China’s carbon dioxide emissions. Zhang et al ( 2021 ) pointed out that the energy intensity of Chinese exports was higher than that of domestically consumed products, which further reflected the tendency of China’s export trade structure to be highly energy-dependent. Moreover, the signing of the Kyoto Protocol also reflected the pressure on China’s international trade competitive position that the rapid growth of greenhouse gas emissions has brought.…”
Section: Introductionmentioning
confidence: 99%
“…While the extant literature provides useful insights into the impact of export trade structure on carbon dioxide emissions (Liu et al 2018 , 2020 ; Tang et al 2016 ; Zhang et al 2021 ), there has been the generation of limited knowledge on the impact of the expansion of high-tech product exports in a region on the total carbon performance of the region. Since China has officially entered the strategic track of achieving peak carbon dioxide emissions, China’s provincial regions will have to consider the issue of achieving peak carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%